HOSPITAL LENGTH OF STAY IN SEPSIS PATIENTS ACROSS AGE, COMORBIDITY, AND INVASIVE DEVICE USE CATEGORIES - Sutanto, Heri; Izzati, Alif Nurul; Mustika, Syifa (Folia Medica Indonesiana, 2025)
Sepsis is a life-threatening condition caused by a dysregulated response of the body to infection. Sepsis is closely associated with high costs and prolonged length of hospitalization. The purpose of this study was to determine the correlation between sepsis risk factors and length of hospitalization for sepsis patients at Dr. Saiful Anwar Malang General Hospital. This study used a retrospective cohort approach with a sample size of 56 medical records. The study used inclusion criteria for sample selection. The analysis results in a p-value of 0.976 and an r-value of 0.004; the findings demonstrated a correlation between patient age and length of hospitalization. A p-value of 0.634 and an r-value of –0.065 indicated a correlation between comorbidities and length of hospitalization. The p-value was 0.101, and the r-value was 0.222, indicating a correlation with the use of intrusive devices. This result suggests that the length of hospitalization for sepsis patients at Dr. Saiful Anwar General Hospital in Malang was not significantly correlated with sepsis risk factors, including age, comorbidities, and the use of invasive devices. Therefore, it is also necessary to examine the admission diagnosis, the SOFA score, and the quantity and duration of invasive device use.